Fostering Students’ Speaking Competence Through Technology Integrated Peer Assessment Technique - Pricilia, Gabby Maureen; Pasaribu, Rahmaini; Davinna, Raysha; Hasibuan, Fitri; Ritonga, Aulia Fitrah Ananda (ITScience (Information Technology and Science), 2026)
The study’s objectives were to determine the extent to which peer assessment techniques are used to teach students how to express their opinions, the degree to which students’ speaking abilities before and after using these techniques differ, and whether there is a significant effect on students’ speaking abilities. There were 38 students in the sample, which was taken by total sampling. The research method was the experimental method (pretest posttest one group design). Data were gathered by speaking test and observation. According to the data analysis, the mean score of students’ speaking skills in expressing opinions before and after using the peer assessment technique was classified as ‘fail’, then after was ‘bad’. The average of using the peer assessment technique in teaching speaking skills in giving opinions is 95%, classified as ‘very good’. Furthermore, based on inferential statistics by using the Wilcoxon Test (non-parametric statistics because the data is not normally distributed), the result shows the significance value was less than 0.05 (0.00<0.05). It means there is a significant effect of using the peer assessment technique on students’ speaking skills in giving opinions.